EVALUATION OF EMERGENCY REVASCULARISATION IN VASCULAR TRAUMA - Khan, Mohammad Iqbal; Khan, Najam; Abbasi, Shafquat Ali; Baqai, Mohammad Tariq; Rehman, Bashir ur; Wayne, Abdul (Journal of Ayub Medical College Abbottabad, 2005)
Background: Vascular trauma is a common life threatening injury leading to serious consequences if not timely and efficiently managed. We evaluated early surgical interventions aimed at revascularization and thus salvaging limb/ organ in life threatening vascular injuries. Aims of our study were to evaluate the outcome of available diagnostic modalities, earliest possible surgical intervention and rate of related complications with particular reference to our existing situation. Methods: Emergency diagnostic workup based mainly on clinical evaluations and required laboratory and imaging parameters leading to revascularisation was performed in 48 patients in Combined Military Hospital (CMH) Muzaffarabad and Islamic Medical College Hospitals between June 1997 and December 2001. Data was collected on pre-designed computerized proforma’s which were completed by the treating surgeon and data was entered and analyzed accordingly. Results: Out of the total 48 patients who sustained major vascular injuries during this period, 14 (29.2%) were having injury to upper limb vessels, 26 (54.2%) patients had injury to the lower limb vessels, 6 (12.5%) patients reported with injury to abdominal vessels. One (2%) patient had injury to common carotid artery, while an other patient to thoracic aorta respectively (2%). Penetrating trauma caused 38 (79%) and blunt trauma caused 10 (21%) major vascular injuries. Out of 48 patients, 41 (85.4%) patients were successful managed by vascular reconstruction without any residual disability. Conclusion: Speedy diagnostic work up and early revascularization yields favourable outcome in vast majority of patients requiring vascular repair. Selections of surgical technique including use of autologous vein graft or artificial vascular graft can save many limbs. In order to achieve good results the time lapse between injury and revascularisation should be less than 6 hours. Key words: vascular injury, emergency revascularisations, limb umasalvage.